ANALISIS HUKUM TERHADAP PELANGGARAN HAK CIPTA PENGGUNA MEDIA SOCIAL APLIKASI TIKTOK DITINJAU MENURUT UNDANG-UNDANG NOMOR 28 TAHUN 2014 TENTANG HAK CIPTA - Sumarjo Makitulung; Arrisman (JOURNAL OF LAW AND NATION, 2023)
The use of the TikTok application in practice reaps pros and cons, because the TikTok application has a feature for uploading songs using songs from the application users themselves, which sometimes users do not do permission for the songs uploaded to the application. The problems in this research are How to identify copyright infringement by users of the TikTok application?, What is the legal protection for creators/copyright holders in the event that their songs are used in the TikTok application without approval according to Law Number 28 of 2014 concerning Copyright?, What is accountability? law on TikTok application users for copyrighted songs used in the TikTok application without the consent of the creator/copyright holder according to Law Number 28 of 2014 concerning Copyright?. The research method used is the juridical normative method, namely the researcher will analyze based on secondary data which includes laws and books. The results of the research show that the identification of copyright infringement by users of the TikTok application according to Law Number 28 of 2014 concerning Copyright, namely violating moral rights and economic rights. Legal protection for creators/copyright holders in the event that their song is used in the TikTok application without approval according to Law Number 28 of 2014 is that the copyright holder has the right to take legal action through litigation/court and non-litigation/settlement outside the court. These legal efforts are criminal and civil legal efforts. The legal responsibility of TikTok application users for copyright infringement in the TikTok application according to Law Number 28 of 2014 can be distinguished in the criminal and civil domains.